(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Recently, researchers have been interested in incorporating a third component into the active layer of organic solar cells (OSC). Introducing a third component aims to improve the efficiency of light absorption, charge separation, and transport within the solar cell. It is widely observed that varying active layer thicknesses result in different device competencies due to the behaviour of charge transportation and charge collection in such volume morphology of active layer. This paper incorporated layer-by-layer (LbL) devices based on BTR-Cl as donor and IT-2Cl as acceptor with Y6 acceptor as a third component in the active layer. These devices had been electrically characterized using organic and hybrid material nano (OghmaNano) simulation tool. A thickness ranging between 40 nm and 100 nm of each material in the active layer was evaluated in this simulation. This simulation shows the current-voltage (I-V) characteristics for ternary LbL OSC devices at various thicknesses. The short circuit current density (Jsc), open circuit voltage (Voc), and fill factor (FF) for each device’s active layer thickness were also provided. At a thickness ratio of 50:60:50 nm (BTR-Cl to Y6 to IT-2Cl) and 100 mW cm-2, AM1.5 incident solar radiance, the maximum attainable efficiency, 12.1%, was found.